2022
DOI: 10.1038/s41467-022-32600-w
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic phonon transport across atomically sharp metal/semiconductor interfaces

Abstract: Understanding thermal transport across metal/semiconductor interfaces is crucial for the heat dissipation of electronics. The dominant heat carriers in non-metals, phonons, are thought to transport elastically across most interfaces, except for a few extreme cases where the two materials that formed the interface are highly dissimilar with a large difference in Debye temperature. In this work, we show that even for two materials with similar Debye temperatures (Al/Si, Al/GaN), a substantial portion of phonons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The thermal transport across the graphene is essentially contributed by each atom pair via van der Waals atomic interactions, and the theory of atomic interaction density can be employed to probe the underlying mechanism . The atomic pairwise contribution to the thermal conductance across the van der Waals interface can be described by the atomic density of interaction via , n ( d ij ) = true{ .25ex2ex 1 , d ij < r m 2 ( r m / d ij ) 6 ( r m / d ij ) 12 , r m d ij r c 0 , d ij < r c …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal transport across the graphene is essentially contributed by each atom pair via van der Waals atomic interactions, and the theory of atomic interaction density can be employed to probe the underlying mechanism . The atomic pairwise contribution to the thermal conductance across the van der Waals interface can be described by the atomic density of interaction via , n ( d ij ) = true{ .25ex2ex 1 , d ij < r m 2 ( r m / d ij ) 6 ( r m / d ij ) 12 , r m d ij r c 0 , d ij < r c …”
Section: Resultsmentioning
confidence: 99%
“…The thermal transport across the graphene is essentially contributed by each atom pair via van der Waals atomic interactions, and the theory of atomic interaction density can be employed to probe the underlying mechanism. 45 The atomic pairwise contribution to the thermal conductance across the van der Waals interface can be described by the atomic density of interaction via 46,47 The where d ij is the separation distance between atom i in graphene and atom j in the epoxy matrix. r m is the critical distance that corresponds to the minimum potential energy of van der Waals interactions modeled by 12−6 L-J potential and is equal to 2 1/6 σ. σ is the distance parameter in L-J potential; six different L-J parameters have been used to describe the interaction between all epoxy atoms and graphene.…”
Section: Density Of Interactionmentioning
confidence: 99%
“…On the one hand, Hohensee et al 33 show that anharmonic phonon scatterings contribute negligibly to the interfacial thermal conductance of diamond/aluminum. Many other studies, on the other hand, show that anharmonic phonon scatterings can contribute largely to the interfacial thermal conductance for Si/Ge, 8,9,13,34 Ar/heavy Ar, 10,12,13 Si/Al and GaN/Al 20 systems. Most recently, Feng et al 35 showed that the four-phonon scattering becomes important in crystal Si at high temperatures ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the experimental results also show that anharmonic phonon scatterings are important for interfacial thermal transport. 20 Although tremendous progress in quantifying the ITC spectrum at interfaces has been achieved, a systematic investigation of the influence of anharmonicity, asymmetry, and quantum effects at the interface on the ITC spectrum is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In our work, we treat separately the electron, κ e , and phonon, κ ph , contributions to the thermal conductivity and we neglect electron-phonon interactions. 41 The total thermal conductivity, κ tot , increases with temperature for both AA and AB-stackings, with a slightly higher value of κ tot (by approximately 1 nW K −1 ) for AB-junctions, which that arises from the higher κ ph values (Fig. 4(e), (d) and Fig.…”
Section: Thermoelectric Properties Of Zgnr-twistronicsmentioning
confidence: 91%